Analisis Penetapan Evaluasi Generalized System of Preference (GSP) Amerika Serikat Terhadap Indonesia dan Pengaruhnya Terhadap Kesepakatan Perdagangan Dibawah World Trade Organization (WTO - Jodie Jeihan; Tasya Ester Loijens; Intan Ekaningtyas (Jurnal Hukum Lex Generalis, 2020)
Liberalism is a basic principle embraced by the United States in all its policies including trade policy. This principle is also carried out by U.S. President Donald Trump in the form of orientation to bilateral agreements. When viewed from the trade relationship between Indonesia and the United States, the Generalized System of Preference or GSP facility is the only bilateral relationship that Indonesia can run with the United States. GSP is the U.S. policy of waiging import duties on the import of certain goods from developing countries in which case Indonesia is one of them. But it turns out that there is a policy of evaluating the implementation of GSP against Indonesia looking at the trade balance and Indonesia's economic policies that have an impact on the United States. The evaluation has the potential to reduce Indonesia's Bargaining Position in GSP facilities. If it comes to unexpected conditions it can harm Indonesia because of the increase in tariffs imposed on the export sector. The author intends to review the reevaluation policy in terms of international law.